IMPLEMENTASI PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN BUDAYA LITERASI DI SEKOLAH DASAR - Prima Rias Wana (Jurnal Tunas Bangsa, 2018)
This study aims to implement a scientific approach to improve the culture of literacy movements in elementary schools. The school literacy movement was launched by the ministry of education and culture in 2015. The movement has three (3) stages, namely habituation, development, and learning. This type of research is qualitative depskiptif research. The location of this study was at Kincang 02 Elementary School, Jiwan District, Madiun District, East Java Province. The research subjects were the Principal, Teachers, and Students. The research instruments used were interviews, observation, and documentation. The results of this study were implemented a scientific approach implementation program to improve the culture of literacy at SDN Kincang 02. The efforts made by the school in implementing the school literacy movement program were: (1) adding enrichment books, (2) bringing the book closer to students in a way making the reading area and environment rich in text, (3) carrying out various forms of literacy activities, and (4) involving the public in the implementation of literacy movements. (5) The school has a good communication relationship with parents in terms of providing learning motivation to children. The constraints faced by schools in implementing the Literacy Movement are: (1) low awareness of teachers, (2) enrichment books that are suitable for children's needs are difficult to find, (3) teachers are lazy to read, (4) teachers do not understand the application of literacy movements, and (5) schools lack funding. Thus, the implementation of the scientific approach The school literacy at SDN Kincang 02 needs to be increased to the development stage by involving various parties. Abstrak Penelitian ini bertujuan untuk mengimplentasikan pendekatan saintifik guna meningkatkan budaya gerakan literasi di sekolah dasar . Gerakan literasi sekolah telah diluncurkan oleh kementerian pendidikan dan kebudayaan pada tahun 2015. Gerakan ini memiliki tiga (3) tahapan, yaitu pembiasaan, pengembangan, dan pembelajaran. Jenis penelitian ini adalah penelitian depskiptif kualitatif. Lokasi penelitian ini berada di SDN Kincang 02, Kecamatan Jiwan, Kabupaten Madiun, Propinsi Jawa Timur. Subjek penelitian adalah Kepala Sekolah, Guru, dan Peserta Didik. Instrumen penelitian yang digunakan adalah wawancara, observasi, dan dokumentasi. Hasil penelitian ini adalah telah dilaksanakan progam implementasi pendekatan saintifik dalam meningkatkan budaya literasi di SDN Kincang 02. Upaya-upaya yang dilakukan sekolah dalam melaksanakan program gerakan literasi sekolah adalah: (1) menambah buku pengayaan, (2) mendekatkan buku ke peserta didik dengan cara membuat area baca dan lingkungan yang kaya akan teks, (3) melaksanakan berbagai bentuk kegiatan literasi, dan (4) melibatkan publik dalam pelaksanaan gerakan literasi. (5) Pihak sekolah sudah memiliki hubungan komunikasi yang baik dengan orang tua dalam hal memberikan motivasi belajar pada anak. Adapun kendala yang dihadapi sekolah dalam pelaksanaan Gerakan Literasi ini adalalah: (1) rendahnya kesadaran guru, (2) buku pengayaan yang sesuai dengan kebutuhan anak sulit ditemukan, (3) guru malas membaca, (4) guru tidak memahami penerapan gerakan literasi, dan (5) sekolah kekurangan dana. Dengan demikian, implementasi pendekatan saintifik pada gerakan literasi sekolah di SDN Kincang 02 perlu ditingkatkan ke tahap pengembangan dengan melibatkan berbagai pihak. Kata Kunci: implementasi, saintifik, literasi